Mercury Anomalies Link to Extensive Volcanism Across the Late Devonian Frasnian–Famennian Boundary in South China - Zhang, Jiawei; Deng, Changzhou; Liu, Weipeng; Tang, Zuoqi; Wang, Yue; Ye, Taiping; Liang, Weian; Liu, Lingyun (Frontiers in Earth Science, 2021)
The Late Devonian Frasnian-Famennian (F-F) mass extinction has been long-time debated by non-volcanic causes, extra-terrestrial impacts, and large igneous provinces (LIPs) eruptions. To better understand the ultimate cause of the F-F mass extinction, here we investigate the chemostratigraphy of mercury (Hg) and total organic carbon (TOC) on two marine F-F strata in the Dushan area, South China. In both sections, high Hg and Hg/TOC anomalies were observed near the F-F boundary. These anomalies are in line with those recently observed in Morocco, Germany, Poland and north Russia, suggesting a global phenomenon. The Late Devonian LIPs eruption, which is believed to have emitted massive amounts of Hg, could be responsible for the global Hg and Hg/TOC anomalies around the F-F boundary. The observed Hg and Hg/TOC anomalies coincide with the extinction of Frasnian fauna in the Dushan area, implying a causal link between the Viluy, Kola and Pripyat-Dnieper-Donets LIPs eruption and the F-F mass extinction.